2022
DOI: 10.3390/ani12162102
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of tRNA-Derived Small RNAs and microRNAs Associated with Immunocompromise in an Intrauterine Growth-Restricted Pig Model

Abstract: Intrauterine growth restriction (IUGR) is an important cause of newborn morbidity and mortality in mammals. Transfer RNA-derived small RNA (tsRNA) has become an emerging non-coding RNA in recent years. tsRNA and microRNAs (miRNAs) share similar mechanisms, which are involved in various biological processes. In this study, the pig was used as a model of IUGR, and the tsRNA and miRNA expression profile in the spleen was characterized by RNA sequencing. A total of 361 miRNAs and 620 tsRNAs were identified, of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Sequencing was performed on an Illumina Nextseq 500 system. The sequencing data were processed as we described before [41,42]. Clean data were obtained by removing raw-data adapters and low-quality readings.…”
Section: Small Rna Sequencingmentioning
confidence: 99%
“…Sequencing was performed on an Illumina Nextseq 500 system. The sequencing data were processed as we described before [41,42]. Clean data were obtained by removing raw-data adapters and low-quality readings.…”
Section: Small Rna Sequencingmentioning
confidence: 99%
“…Studies have shown that PSC‐derived exosomes promote PC proliferation, migration, and drug resistance by delivering proteins, mRNA, and non‐coding RNA, leading to changes in gene profiles and activation of oncogenic pathways 8–10 . It has been reported that small ncRNAs can be derived from the precursors and mature sequences of small RNAs derived from tRNAs (tDRs) 11,12 . RNA polymerase III transcribes tRNAs, which are typically 76–90 nucleotides long in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…8 , 9 , 10 It has been reported that small ncRNAs can be derived from the precursors and mature sequences of small RNAs derived from tRNAs (tDRs). 11 , 12 RNA polymerase III transcribes tRNAs, which are typically 76–90 nucleotides long in eukaryotes. It has been found that pre‐tRNAs and mature tRNAs are extensively modified before and after they are exported to the cytoplasm in order to create two different kinds of can generally be divided into tRNA halves (tiRNAs) and tRNA‐derived fragments (tRFs).…”
Section: Introductionmentioning
confidence: 99%